Еколого-фізіологічна та фітопатологічна оцінка рослинного покриву м. Ковеля в умовах урбанізації - Голуб, Валентина; Голуб, Сергій; Golub, Valentyna; Golub, Sergii (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті викладено результати комплексного дослідження впливу урбогенних факторів на довкілля. Розглянуто просторову строкатість забруднення важкими металами міських ґрунтів з урахуванням різної потужності джерел забруднення. Досліджено негативний вплив забруднення токсичними елементами дерново-підзолистого ґрунту на ріст та розвиток зелених насаджень м. Ковеля. Здійснено інвентаризацію видів міських рослин і проаналізовано морфофізіологічні зміни в деревних і трав’яних рослин, їх фенологію й життєвість в умовах техногенного пресу. Обґрунтовано та рекомендовано для озеленення такі види деревних рослин, які зменшують негативний вплив полютантів на довкілля. The article presents the results of a comprehensive study of the impact of urbogennyh factors on the environment. The spatial heterogeneity of urban soil pollution with heavy metals, taking into account the intensity of pollution sources. Studies have confirmed that the soil urboehkosistemy city Kovel over time significantly anthropogenically altered by major agrochemical indexes.Studied the negative impact of pollution with toxic elements sod-podzolic soils on the growth and development of the green spaces of the city of Kovel. It made an inventory of urban vegetation and analyzed the morphological and physiological changes in woody and herbaceous plants, their phenology and biological stability in the conditions of anthropogenic press. It is proved that the most resistant wood species in the industrial area of Kovel are common spruce, alder sticky, silver birch, ash, common maple holly, and least of all turned out to be resistant chestnut horse. Substantiated and recommended a number of plant species in order to reduce the negative impact on the environment polyutantov.
Ecological, Physiological and Phytopathological Assessment of Vegetation Under Urbanization Kovel
Keywords: heavy metals; accumulation; green plantations; urbogennye factors; важкі метали; акумуляція; зелені насадження; урбогенні фактори